Chinese dentists’ restorative preferences and choices for endodontically treated teeth: a representative survey - Li, Wenhui; Zheng, Ziting; Zeng, Yuting; Zhou, Zhiyan; Xiao, Ping; Zhong, Xincen; Yan, Wenjuan (BMC oral health, 2024)
The optimal restoration protocol for endodontically treated teeth (ETT) remains a subject of debate. This survey aims to assess the current level of awareness, knowledge, and prevailing opinions among dental practitioners in China regarding the application of endocrown versus the post/core/crown ensemble for post-endodontic restoration strategies. A validated questionnaire, encompassing three sections, was distributed electronically to dentists practicing in China. The initial section collected demographic characteristics of the participants, while the subsequent sections assessed their knowledge and preferences regarding ETT restoration techniques in various clinical scenarios. Distribution of the survey was facilitated through the social media platform WeChat, with a total of 600 invitations sent out. Data analysis was conducted using SPSS Statistical Software, employing frequency and Chi-square tests to determine statistical significance at the P < 0.05 threshold. A total of 400 valid questionnaires were collected. The amount of remaining tooth structure was identified as the most influential factor in determining the restoration strategies, contributing to 26.1%. Over 72.8% of the surveyed dentists acknowledged the reinforcing effect of intraradicular posts on ETT. More than half of the participants reported the application of endocrowns within their post-endodontics management. The preference for endocrowns was pronounced in cases where more than 50% of the tooth's structure remained or when occlusal space limitations were present. The Chi-Square test revealed that the participants' knowledge regarding endocrown restoration was significantly influenced by their age, educational background, and experience (p < 0.05). The clinical decision-making process for the restoration of endodontically treated teeth (ETT) by dental practitioners primarily relies on the amount of remaining tooth structure. Most surveyed dentists believe that the presence of a post can reinforce ETT. A majority of participants consider the Endocrown as a viable alternative restorative treatment for ETT.